Sofosbuvir‐based therapies in genotype 2 hepatitis C virus cirrhosis: A real‐life experience with focus on ribavirin dose - Carlo Smirne; Antonio D'Avolio; Mattia Bellan; Alessandro Gualerzi; Maria G. Crobu; Mario Pirisi (Wiley, 2021)
Abstract This study aimed to investigate the efficacy and safety of sofosbuvir‐based therapies for the treatment of cirrhosis from hepatitis C virus (HCV) genotype 2 infection. Data of all consecutive HCV genotype 2 cirrhotic patients who started sofosbuvir‐based treatments between January 2015 and March 2017 in eight Italian tertiary hospitals were collected retrospectively. Overall, 273 patients (Child A: 94.5%) were enrolled. In the 194 subjects treated with sofosbuvir/ribavirin, median initial ribavirin dosage was 13.9 mg/kg/day, and therapy duration was 16 weeks. Sustained virological response (SVR) rates were 93.8% in intention‐to‐treat (ITT) and 95.3% in per‐protocol (PP) analyses for the 129 treatment‐naïve patients, and 96.9% (ITT) and 98.4% (PP) for the 65 treatment‐experienced subjects. Adverse events were reported in 142 patients (73.2%), but only 1.5% discontinued treatment. Eighty‐eight subjects with treatment‐induced anemia (mild: 34.5%, moderate: 7.7%, severe: 3.1%) had to reduce ribavirin dosage, but SVR rates were comparable to the weight‐based dose group, both in ITT (95.4% and 94.3%) and PP (97.7% and 95.2%) analyses, respectively. Moreover, ITT and PP SVR rates were similar between shorter (<20 weeks) (94.1% and 96.0%, respectively) and prolonged (≥20 weeks) regimens (95.7% and 96.7%, respectively). SVR rates in the 79 subjects treated with sofosbuvir/daclatasvir (without ribavirin) were similar (ITT: 96.2%; PP: 97.4%, respectively), without de novo/worsening anemia. In conclusion, in a real‐life study centered on genotype 2 patients with well‐compensated cirrhosis, sofosbuvir‐based regimens were associated with good SVR and tolerability rates, regardless of previous antiviral treatments, without a significant impact of on treatment ribavirin dose reductions.